ANALISIS PROFITABILITAS, KEBIJAKAN DIVIDEN, PENANAMAN MODAL ASING, SKALA DAN UMUR PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2009-2011 (Students' Journal of Accounting and Banking, 2013)
The company's main goal according to the theory of the firm is to maximize wealth or firm value (value of the firm). Maximize the value of the company is very important for a company, because by maximizing the value of the company means also maximizing shareholder wealth is the main goal of the company.This study aimed to determine the effect of profitability, dividend policy, foreign investment, enterprise scale and firm age on firm value in the companies listed in Indonesia Stock Exchange.This study uses secondary data from annual reports obtained from BEI, www.bapepam.go.id and www.idx.co.id as well as from the Indonesian Capital Market Directory (ICMD). Samples were selected using purposive sampling technique to the study period 2009-2011. Data were analyzed using multiple linear regression analysis. The test results indicate that the hypothesis of profitability, dividend policy, enterprise scale and age of the company and significant positive effect on firm value. While foreign investment and significant negative effect on firm value.Keywords: profitability, dividend policy, foreign investment, corporate scale, firm age and firm value